Hak Konstitusional untuk Berunjuk Rasa dan Standar Penggunaan Kekuatan Aparat pada Gelombang Aksi 2025 (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the constitutional right to protest and the legal standards governing the use of force by state apparatus during the 2025 protest waves in Indonesia. The issue is constitutionally important because a democratic rule-of-law state must simultaneously protect freedom of assembly and ensure that law enforcement action remains bound by legality, necessity, and proportionality. Using normative legal research with statutory, conceptual, and human-rights approaches, this article analyses the 1945 Constitution, Law Number 9 of 1998, Law Number 39 of 1999, Law Number 2 of 2002, Law Number 12 of 2005, and the regulatory framework on police use of force, supported by relevant legal scholarship and international standards. The article argues that Indonesian law already recognizes the right to assemble and imposes human-rights obligations on policing, but normative gaps and weak accountability still allow excessive or indiscriminate force in crowd control. Therefore, the legal framework must be read through a stricter standard of legality, necessity, proportionality, escalation, reporting, and effective review of force incidents.